Isolation, Identification and Molecular Characterisation of Aeromonas Species from Fish - Ahmad, Noorlis (2001)
A total of 60 isolates of Aeromonas species which were originally isolated from various fish samples obtained from wet markets in Selangor were examined and further characterised by both phenotypic (antibiotics resistance and hemolysis assay) and genotypic (plasmid profiling, RAPD pattern and SDS-PAGE) methods. All the isolates examined in this study exhibited multiple antibiotic resistance pattern to antibiotics (ampicillin (98.4%), carbenicillin (93.6%), erythomycin (91.9010), bacitracin (87.1%), streptomycin (74.2%), kanamycin (58.1%), gentamycin (53.2%), tetracycline (46.8%), cephalothin (33.9010), nalidixic acid (25.8%), ceftriaxone (76.1%), cefoperazone (14.5%) and ceptazidime (8.06%» tested. Plasmid analysis showed that 38.3%, 20%, 16.7% and 8.3% of isolates from Ikan Tilapia Merah, Ikan Keli, Ikan Terubuk and Ikan Merah respectively contained plasmid DNA bands with sizes ranging from 1.7 to 10.4 megadalton (MDa). Based on their plasmid profiles, the isolates of the Aeromonas species isolates were grouped into 18 plasmid patterns. Three 10-mer oligonucleotides primers GEN 1-50-02 (5'-CAATGCGTCT-3'), GENI-50-06 (5'-CGGATAACTG-5')and GENl-SO-08 (5'-GGAAGACAAC-3') were used to amplify genomic DNA. The profiles observed after electrophoretic separation for the 3 primers when combined together were able to distinguish the Aeromonas species isolates into 4 major clusters, respectively. In haemolysis assays of Aeromonas species, 71. 7% were observed to be alpha (a.), 21.7% were beta «(3) and only 6.7% were gamma (y) haemolytic. The SDSPAGE of whole cell protein pattern analysis indicated that the strains of Aeromonas hydrophila group have a dominant band of variable molecular weight between 25 to 67 kDa. Thus, the strains of Aeromonas species examined from various types of fish are genotypically diverse as shown by RAPD and SDS-PAGE protein pattern, suggesting that different strains have been brought into this geographical region or strains already present have continued to evolve. These results suggest that RAPD-PCR assay and SDSPAGE whole cell protein pattern are more powerful methods than plasmid profiling and antibiotic resistance technique for discriminating Aeromonas species. Thus, RAPD-PCR assay and SDS-P AGE whole cell protein can be used as a valuable tool for epidemiological studies.